The credential society : an historical sociology of education and stratification - Collins, Randall, 1941- (Legacy editions (Columbia University. Press), 2019)
The Credential Society by Randall Collins is a classic on higher education and its role in American society. Forty years later, its controversial claim that the expansion of American education has not increased social mobility, but created a cycle of credential inflation, has proven remarkably prescient